ERROR ANALYSIS OF THE STUDENTS IN USING SIMPLE PRESENT TENSE WRITING DESCRIPTIVE TEXT - Christian Nenni Purba; Bertaria Sohnata Hutauruk (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2022)
This research is about Error analysis of using simple present tense made by the students in writing descriptive text at grade II in junior high school Pematangsiantar. The problem is to find out the In this study, the researcher uses qualitative method. The students of grade VIII SMP Negeri 2 Siantar is 20 students taken the subject. The instrument types of error analysis found on the students writing descriptive text. The researcher asks the students to write descriptive text in using simple present tense. The result of the research is there are four types of error made by the students writing in using simple present tense based description of error, they are: (1) omission (45,23%), (2). error of addition (8,33%), (3). error of misinformation (20,23%), and ()4. error of misordering (26,19%). From the results of the analysis, it was found The two errors that have the highest number is omission(45,23%). The conclusion is there are still many students who do not understand how to make sentences using the simple present tense in descriptive text and practice again to using tobe (is, am are) in sentence, use of verb s/-es and regular and irregular verb. For students, they should learn more again and discuss with their friends in group and practice it.